Tumor Volume Predicts High-Risk Patients and Guides Initial Chemoradiotherapy for Early Cervical Cancer - Zhang, Jingjing; Cao, Dongyan; Yang, Jiaxin; Shen, Keng; He, Yonglan; Xue, Huadan (Frontiers in Oncology, 2021)
We evaluated the relationship between the minimum tumor-free margin, tumor volume, and adverse pathological risk factors in early cervical cancer and explored the predictive value of these parameters for different types of risk patients to guide individualized therapeutic strategies. Patients who received the initial treatment of radical operation of cervical cancer and their postoperative pathological reports in our hospital from July 1, 2017, to June 30, 2019, were reviewed. Their minimum tumor-free margin and tumor volume were measured on preoperative magnetic resonance imaging. Student’s t-test and the receiver operating characteristic curve analysis were used for data analysis. A total of 240 patients were included. Adverse pathological risk factors were as follows: deep cervical infiltration, 95 (39.6%) cases; lymph vascular space invasion, 91 (37.9%); lymph node metastasis, 20 (8.3%); parametrial infiltration, 8 (3.3%); tumor diameter ≥4 cm, 7 (2.9%); and positive surgical margin, 1 (0.4%). According to the adverse pathological factors, there were 20 (8.3%) high-risk patients, 50 (20.8%) medium-risk patients, and 170 (70.8%) low-risk patients. The ranges of the minimum tumor-free margin and tumor volume were 0.01–13.5 mm and 105–27,990 mm3, respectively. The minimum tumor-free margin with lymph node metastasis was significantly smaller than that without (P <0.05). The tumor volume with parametrial infiltration, deep cervical infiltration, or lymph vascular space invasion was significantly greater than that without (P < 0.05). The tumor volume was significantly different among low-, medium-, and high-risk patients (P <0.05). Tumor volume was of predictive value for high-risk patients (P < 0.05). With 3,505 mm3 as the cutoff value, the sensitivity and specificity for the prediction of high-risk patients were 88.9% and 84.8%, respectively. Tumor volume can be used as a great predictor of high-risk patients (cutoff value, 3,505 mm3), which could be an indication of initial chemoradiotherapy for early cervical cancer.